Analisis Degradasi Performa Marka Jalan Thermoplastik Pada Jalan Tol - Yogi Oktopianto; Rukman Rukman (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2021)
The program for maintenance and replacement of toll road surface markings aims at meeting the standards of performance set out in the Minimum Service Standards regarding for the substance of safety for road guidance indicators, which is road surface markings for the safety and comfort of toll road users. Good visibility of the road surface markings is necessary as it helps reducing the chance of traffic accidents. The problem encountered is a drastic decrease in the reflectivity level of road surface markings in a short time. The study was conducted to determine the degradation of the value of road surface markings reflectivity during the service life of the maintenance methods on the routine and periodic markers. The research was conducted experimentally by making a mock up and testing the reflectivity at the existing location using a reflectometer on 2 test models. The results showed a reflectivity degradation was 43% in the marking method carried out directly over the old road surface markings with an average reflectivity value of 401 mcd/m2/lux. This study concluded the road surface markings applied to the asphalt pavement. The thermoplastic material against the glass bead binds perfectly, while the road surface markings painted on the old road surface markings of the thermoplastic material against the glass bead do not bind properly so that the glass beads are easily detached